2012
DOI: 10.1371/journal.pone.0038280
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic Protein G0S2 Maintains Quiescence in Hematopoietic Stem Cells

Abstract: Bone marrow hematopoietic stem cells (HSCs) balance proliferation and differentiation by integrating complex transcriptional and post-translational mechanisms regulated by cell intrinsic and extrinsic factors. We found that transcripts of G0/G1 switch gene 2 (G0S2) are enriched in lineage− Sca-1+ c-kit+ (LSK) CD150+ CD48− CD41− cells, a population highly enriched for quiescent HSCs, whereas G0S2 expression is suppressed in dividing LSK CD150+ CD48− cells. Gain-of-function analyses using retroviral expression v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 51 publications
1
85
0
Order By: Relevance
“…A limited number of studies have implied that G0s2 is involved in cell proliferation (33), differentiation (19), apoptosis (34), inflammation (35), and lipid metabolism (36) in various cellular settings. Moreover, G0s2 was reported to localize to the cytosol (33), endoplasmic reticulum (19), mitochondria (34), or the surface of lipid droplets (36).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have implied that G0s2 is involved in cell proliferation (33), differentiation (19), apoptosis (34), inflammation (35), and lipid metabolism (36) in various cellular settings. Moreover, G0s2 was reported to localize to the cytosol (33), endoplasmic reticulum (19), mitochondria (34), or the surface of lipid droplets (36).…”
Section: Discussionmentioning
confidence: 99%
“…7 In hematopoietic progenitor cells as well as in human APL cell line, G0S2 was also found to bind to nucleolin, which is known to be involved in rRNA synthesis, chromatin remodeling and cell proliferation. 5,27,28 This binding results in the cytoplasmic retention of nucleolin and decreased proliferation of these cells. 5,27 Given accumulating evidence for G0S2 as a potential tumor suppressor, we are planning to examine the in vivo effect of G0S2 loss on tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…5,27,28 This binding results in the cytoplasmic retention of nucleolin and decreased proliferation of these cells. 5,27 Given accumulating evidence for G0S2 as a potential tumor suppressor, we are planning to examine the in vivo effect of G0S2 loss on tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein was initially identifi ed in 1991 to be transiently expressed in lymphocytes during the switch from the G0 to the G1 phase of the cell cycle ( 14 ). A very recent study reported that G0S2 interacts with nucleolin, resulting in its cytosolic retention and thereby leading to reduced proliferation of hematopoetic stem cells ( 15 ). The role of G0S2 in the cell cycle remains unknown, but the protein was shown to be involved in apoptosis ( 16 ).…”
Section: Sequence Analysismentioning
confidence: 99%